2021
DOI: 10.1111/1440-1630.12758
|View full text |Cite
|
Sign up to set email alerts
|

Goal setting for people with mild cognitive impairment or dementia in rehabilitation: A scoping review

Abstract: Introduction Goal setting is an integral part of the rehabilitation process and assists occupational therapists to target therapy towards achieving meaningful outcomes. People with mild cognitive impairment or dementia may experience barriers participating in goal setting due to preconceptions that the person cannot participate owing to changes in both cognitive and communicative abilities. The aim of this review was to identify goal setting approaches, common goals identified, and enablers and barriers to goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…This suggests that across older adult populations with neurodegenerative disease experiencing dementia or cognitive impairment, GAS may be able to detect clinically meaningful change and may be responsive to measuring progress toward functional patient-centered goals related to communication, cognition, QOL, or ADLs. These findings are consistent with other systematic reviews suggesting that GAS is responsive to functional change in geriatric rehabilitation [8, 20] and in adults with cognitive impairment [23]. While these reviews did not specifically evaluate GAS in older adults with neurodegenerative disease experiencing dementia or cognitive impairment, responsiveness trends are similar between this study and the studies mentioned above (i.e., statistically significant pre- and post-intervention GAS scores).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that across older adult populations with neurodegenerative disease experiencing dementia or cognitive impairment, GAS may be able to detect clinically meaningful change and may be responsive to measuring progress toward functional patient-centered goals related to communication, cognition, QOL, or ADLs. These findings are consistent with other systematic reviews suggesting that GAS is responsive to functional change in geriatric rehabilitation [8, 20] and in adults with cognitive impairment [23]. While these reviews did not specifically evaluate GAS in older adults with neurodegenerative disease experiencing dementia or cognitive impairment, responsiveness trends are similar between this study and the studies mentioned above (i.e., statistically significant pre- and post-intervention GAS scores).…”
Section: Discussionsupporting
confidence: 91%
“…No other studies reported metrics for reliability or validity. This is consistent with other systematic and scoping reviews that have found sparse reporting on the validity and reliability of GAS use in rehabilitation research [33] and in adults with communication disorders [9], MCI, or dementia [8]. One systematic review of GAS use in geriatric rehabilitation [20] found that GAS showed high concurrent, content, and predictive validity, as well as high inter-rater reliability.…”
Section: Discussionsupporting
confidence: 85%
“…Six of the identified tools were described and studied in five or more articles. These included Goal Attainment Scaling including Goal Attainment Scaling for Major Depressive Disorder and Goal Attainment Scaling for Upper Limb Spasticity 2857,113,114,118143,150,172,181 ( n = 61), Canadian Occupational Performance Measure 6,2527,101,103…”
Section: Resultsmentioning
confidence: 99%
“…Only five of the identified tools made use of information and communications technology for goal setting, four of which were categorized as tools for goal selection and goal documentation. These included Canadian Occupational Performance Measure, 6,2527,101,103114,142,171,175,176 Goal Attainment Scaling, 2857,113,114,118<...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation